Intoxication with massive doses of amlodipine and candesartan requiring venoarterial extracorporeal membrane oxygenation - Minagawa Yusuke; Yamana Hidetoshi; Tsutsumi Yusuke; Ishigami Koji; Togo Masahito; Yasuda Susumu; Ogura Takayuki (Acute Medicine & Surgery, 2023)
Abstract Background Calcium channel blockers and angiotensin II receptor blockers are commonly prescribed to treat hypertension. Massive overdoses can cause both distributive and cardiogenic shock because of their effects on vascular smooth muscles and severe myocardial depression. Case Presentation We present the case of a 46‐year‐old man who was brought to our emergency department after ingesting 1210 mg amlodipine and 936 mg candesartan. The patient's hemodynamic status deteriorated despite treatment with vasopressors, calcium gluconate, and hyperinsulinemia‐euglycemia therapy with mechanical ventilation. Venoarterial extracorporeal membrane oxygenation was initiated for refractory shock. The patient was weaned off extracorporeal membrane oxygenation on day 5 and discharged on day 18 of hospitalization. Conclusion When medical therapies are ineffective, aggressive venoarterial extracorporeal membrane oxygenation should be considered for the management of refractory shock in the setting of calcium channel blocker with angiotensin II receptor blocker overdose.